Translation Techniques Used by Google Translate and Naver Papago in @Akunyakul Twitter Account - Andriani, Delvi Gia; Setyaningsih, Nina (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
The research aims to analyze the translation techniques and find similarities and differences between Google Translate provided by Twitter and Naver Papago ability to translate the nonstandard word contained in @akunyakul’s tweet. This research used Molina & Albir’s (2002) framework to analyze the type of translation techniques applied in translating 131 nonstandard words. The results reveal that there are 6 translation techniques used in translating nonstandard words: adaptation, established equivalent, generalization, literal translation, particularization, and transposition. The most applied translation technique is literal translation since the machines do not understand the context and language style of the tweets. Based on the analysis, the similarities are both machines generally apply the same technique to translate nonstandard words. Meanwhile, the difference is that Google Translate provided by Twitter succeeded in translating more nonstandard words than did Naver Papago. Therefore, it can be said that Google Translate provided by Twitter is better able to translate nonstandard words than Naver Papago. This research suggests that translation machines especially Google Translate provided by Twitter and Naver Papago improve their ability to translate nonstandard words, especially in terms of local language, shortened forms, gestures, common particles, slang words, and writing style.